Intelligent Tutoring Systems in Higher Education - Towards Enhanced Dimensions - Bledar Fazlija (Forum Neue Medien in der Lehre Austria, 2019)
This paper describes how intelligent tutoring systems (ITSs) improve flexible learning in higher education. The benefits of ITSs over course management systems (CMSs) are discussed, and we demonstrate how the traditionally used dimensions of flexibility can be enhanced to tackle the challenges that higher education is facing from an abundance of online educational products and services. In addition, a new data-driven approach to analyzing questions about flexible learning is suggested, which could lead to better-optimized settings for flexible learning.